2021
DOI: 10.1371/journal.pone.0257590
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of mothers regarding children’s vaccinations in Cyprus: A cross-sectional study

Abstract: Introduction Vaccine hesitancy is identified as one of the top threats to global health. A significant drop of childhood vaccine coverage is reported worldwide. One of the key reasons that influenced mothers’ choice to postpone, or avoid children’s vaccination, is knowledge. This study aimed to assess the level of Cypriot mothers’ knowledge on certain aspects of vaccination of their children, examine the association between vaccination knowledge and selected socio-demographic factors, and lastly assess the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 53 publications
(42 reference statements)
4
21
2
Order By: Relevance
“…Our study identified a high knowledge level towards childhood vaccination among Greek mothers which is consistent with two other recent studies in Greece [ 32 , 56 ]. Likewise, this finding is in agreement with the results of a recent cross-sectional study that reported a high level of childhood vaccination knowledge among Cypriot mothers [ 31 ]. Pediatricians should be aware of factors, such as the educational level that could influence maternal attitudes towards childhood vaccination and preferred modes of risk-benefit information.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study identified a high knowledge level towards childhood vaccination among Greek mothers which is consistent with two other recent studies in Greece [ 32 , 56 ]. Likewise, this finding is in agreement with the results of a recent cross-sectional study that reported a high level of childhood vaccination knowledge among Cypriot mothers [ 31 ]. Pediatricians should be aware of factors, such as the educational level that could influence maternal attitudes towards childhood vaccination and preferred modes of risk-benefit information.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shows that most mothers vaccinated their child/children, as reflected by the high vaccination coverage (98%). This finding concurs with the results from a previous study in Cyprus that investigated the maternal knowledge towards childhood vaccination, in which 97% of participants reported the vaccination of their children [ 31 ]. Also, another study reported a considerably high percentage of pregnant women in Greece (89%) were likely to vaccinate their child which it was accordance with the National Vaccination Program [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…), information related to COVID-19 vaccination, sources of vaccines information, and participants’ general vaccine knowledge and attitudes towards mandatory vaccination. The questionnaire was developed by our research team, based on our previous research experience and extensive literature search [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Prior to the actual study, face validity was tested in a small pilot study involving 50 participants to assess the clarity and the applicability of all items of the survey, as well as to address wording problems.…”
Section: Methodsmentioning
confidence: 99%
“…Mothers' knowledge has been suggested as a key component in deciding childcare and influencing vaccination decisions for their children. Because women are generally the major decision makers for their children's healthcare, including vaccination, our main study topic is on their immunization knowledge (Kyprianidou et al, 2021). In order to achieve full immunization before a child's first birthday, mothers' knowledge plays a significant role, as do prior parent variables, knowledge attitude, and practice.…”
Section: Introductionmentioning
confidence: 99%